Pendidikan Perawatan Kaki dalam Pencegahan Ulkus Kaki Diabetikum - Yalini, Laksmi; Samiasih, Amin; Armiyati, Yunie (FORIKES, 2024)
Prevention of diabetic ulcers is one of the chronic complications of type 2 diabetes mellitus which is characterized by infection, ulceration, and/or damage to the deepest skin tissue of the feet in sufferers, due to neurological abnormalities and peripheral vascular disorders. The aim of this research was to obtain an overview of methods and strategic interventions for educational foot care to prevent diabetic foot ulcers. This study was a systematic review prepared based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes. The databases used in this research were Google Scholar, ProQuest and PubMed, from 2018 to 2023. The keywords used were